2018
DOI: 10.1111/gcbb.12575
|View full text |Cite
|
Sign up to set email alerts
|

Selection and optimization of a suitable pretreatment method for miscanthus and poplar raw material

Abstract: Miscanthus and poplar are very promising second‐generation feedstocks due to the high growth rates and low nutrient demand. The aim of the study was to develop a systematic approach for choosing suitable pretreatment methods evaluated with the modified severity factor (log R0″). Optimal pretreatment results in a high delignification grade, low cellulose solubilization and increased accessibility for enzymatic hydrolysis while revealing minimal log R0″ values. In order to do so, several reaction approaches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The chemical composition of untreated and HWE hybrid poplar biomass is presented in Table . The HWE conditions were selected based on previous reports, where the pretreatment of poplar species at 160 °C, between 15 and 90 min, facilitated the maximization of xylan recovery without significantly hydrolyzing lignin and cellulose. , As given in Table , increase in HWE severity led to a corresponding decrease in the recovery of pretreated solids, from 10 to 25%. Other studies have also reported a mass loss of 25–48% during hot water pretreatment of hardwoods .…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of untreated and HWE hybrid poplar biomass is presented in Table . The HWE conditions were selected based on previous reports, where the pretreatment of poplar species at 160 °C, between 15 and 90 min, facilitated the maximization of xylan recovery without significantly hydrolyzing lignin and cellulose. , As given in Table , increase in HWE severity led to a corresponding decrease in the recovery of pretreated solids, from 10 to 25%. Other studies have also reported a mass loss of 25–48% during hot water pretreatment of hardwoods .…”
Section: Resultsmentioning
confidence: 99%
“…The ground biomass powders (10 g) were incubated with 5% NaOH at 60 °C for 1 h for 5 times and then treated with 0.5% NaClO at 60 °C for 1 h for 3 times. 34 The solid residues were filtered, washed with distilled water to neutral, and disintegrated using a high-speed blender (Ultra Turrax T18, IKA, Germany) at 11 000 rpm for 5 min at room temperature. The suspension was further homogenized at 60 MPa using a high-pressure homogenizer (HPH) (AH-1500, ATS, Canada) for various cycle times to achieve CNF samples, which are termed HPH-5t, HPH-10t, HPH-20t and HPH-30t corresponding to the homogenized cycles of 5, 10, 20, and 30 times, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Value chains analysed in the modular lignocellulosic biorefinery concept of the Baden‐Württemberg Lignocellulose Research Network. The coloured lines indicate selected value chains described in one of the research articles of this special issue: Seibert‐Ludwig et al () (light blue), Rohde et al () (medium blue), Schuler et al () (dark blue), Siebenhaller et al (), Horlamus et al (), (dark green), Dörsam et al (), Lange et al () (brown). Other data are taken from Lange et al () (medium green)…”
Section: Which Processes May Be Contained In a Future Lignocellulosicmentioning
confidence: 99%
“…In the next step, the dissolved hemicellulose is recovered from the cellulose fibres (Zhang, Pei, & Wang, ). The study of Seibert‐Ludwig, Hahn, Hirth, and Zibek () systematically compared reaction conditions for separation processes applied to miscanthus and poplar wood. The aim was to find the most favourable process conditions to achieve a high grade of delignification and low cellulose solubilization, thus leading to a high availability of cellulose for enzymatic hydrolysis.…”
Section: Which Processes May Be Contained In a Future Lignocellulosicmentioning
confidence: 99%